Estimation of dental caries treatment needs--a review of the literature - Gugushe, T S (SADJ (Houghton), 2000)
If we wish to achieve a better understanding of the treatment needs in the delivery of primary dental services, we need to know why differences in dental caries recorded in the general practice and survey settings occur and the reasons for these differences. We also need to know how this factor influences the volume and type of treatment planned, both for the individual skilled benchmark epidemiologist and practitioner, and for mean world extremes on the other hand. This paper reviews estimates of dental caries treatment needs from the perspective of translation of dental caries status to estimates by need, estimation of need for dental care at the time of examination, differences in caries diagnosis between the epidemiologist and clinician and the consequences thereof, and changes in the presentation of dental caries that have occurred over the years. It is evident from this review of dental caries treatment needs that although the past record of dental epidemiology and clinical diagnosis can be defended, we cannot afford to do what has been done in the past, which was appropriate for lesions seen in the 1960s and 1970s, to the disease as it occurs in the 1990s.